Boldly going… Introducing conflict management training to Starship Children's Hospital. (2nd February 2023) - Miles, Fiona; Barclay, Sarah; Menson, Esse; Shepherd, Toni; Webster, Louise
Abstract : Conflict between health professionals and whānau (families) in paediatric hospitals is common and leads to significant distress for families and staff. The likelihood of challenges and conflict around communication and critical medical decision‐making is increased where there are cultural and social complexities. Training staff to recognise and manage conflict as early as possible improves patient/whānau outcomes and staff well‐being. This article describes an ongoing collaboration between Starship Children's Hospital in Auckland New Zealand (NZ) and the UK Medical Mediation Foundation (MMF) focused on educating staff in the early recognition and management of conflict using mediation skills. An evidence‐based training programme and structured ongoing supervision of a small group of champions has enabled this training to be embedded into Starship clinical practice. The collaboration has included careful consideration of the New Zealand setting, ensuring that the content of the programme specifically addresses our unique cultural and social context. Mediation skills are an important step in ensuring that our patients and whānau feel heard, acknowledged, and respected, and contribute to the Starship Child Health's strategic priority of eliminating inequity and addressing institutional bias.